Managing Anxious Patients Undergoing Magnetic Resonance Imaging: Evidence Versus Common Practice in Ireland - Arsenault, Shane; Keller, Connor (Trinity Student Medical Journal, 2020)
Aim: Adult patients undergoing Magnetic Resonance Imaging (MRI) often experience anxiety prior to and during scanning. While NICE guidelines exist for anxious paediatric patients undergoing MRI procedures, no formal guidelines have been developed for adults. The aim of this study was to compare current practices of managing anxious adult patients undergoing MRI procedures in a selection of Irish hospitals with a reviewed international evidence base. Methods: A comprehensive literature review was conducted once search terms, the Boolean operators with which to pair them, and the parameters of our search were defined. The Cochrane Database, PubMed, Google Scholar and eMedicine databases were all utilised for the literature review. This knowledge base was then used to create a comprehensive survey, which our team used to conduct phone interviews with nine hospitals throughout Ireland regarding their existing protocols. Results: The literature demonstrates the benefits of utilising oral, or if necessary, intravenous sedation in anxious patients, despite the potential adverse effects of such. However, no universally-approved or utilised protocols have been established in Ireland. Our survey of nine Irish hospitals found three hospitals with vague and open-ended departmental protocols. The remainder of surveyed hospitals referred anxious patients to their general practitioner for review prior to repeat scans on a case-by-case basis. Discussion: Our study demonstrates the lack of a nationally implemented formal protocol in Ireland for anxious patients undergoing MRI procedures. Without a formal protocol in place, vague protocols prevail, costing the healthcare system and individual patients time and money. We would aim to build upon this research, consulting with international hospitals to create a formal and robust protocol.